A comparison between women and men : Tarabai Shinde and the critique of gender relations in colonial India - O'Hanlon, Rosalind (Oxford University Press, 1994)
Interest in the history of women and gender relations in India has intensified greatly in recent years. Historians have explored not only the way in which colonial rule shaped this history, but also the significance of gender itself in helping to construct and maintain colonial hegemony.